Exploring the effectiveness of advertising towards brand recall / Noorsyazwani Azri Zulkifli and Anisah Mohamad Razali - Azri Zulkifli, Noorsyazwani; Mohamad Razali, Anisah (Faculty of Business and Management, 2013)
This research was conducted to explore the marketing tool which is the Effectiveness Advertising towards Brand Recall. The population of this research was among the staff of Malaysian Agricultural Research and Development Institute (MARDI) and Radio TelevisyenMalaysia (RTM) Angkasapuri. Researcher and only 150 respondents were chosen by using simple random sampling. This research will be analyzed and examined by using three major independent variables which are advertising frequency, advertising type, and product involvement. Type of analysis in this research involves Pearson correlation, and multiple regression analysis. The result found that there is a significant relationship between independent variables towards the brand recall amongst staffs in MARDI Headquarter and Radio Televisyen Malaysia (RTM).